The significant stress factors that affect the academic performance of BS Accountancy students of the College of Management - Buac, Johaida C.; Clementir, Nowill M.; Diones, Silvestre M., Jr.; Jamili, Joanna Grace S.; Morata, Madonna C.; Saniel, Jan Michael P. (2008.)
Stress can have a significant impact to student's academic performance. In earning grades in a certain semester, stress is but one of the many factors that contribute to success or failure in a student's academic life as measured by the General Weighted Average or GWA. In more demanding degree programs such as BS accountancy, stress can give a greater level of impact to student's academic performance. The researchers have classified the stress factors as academic, financial, social and other factors, and personality type in the hope of finding how significant these factors are in affecting a student's GWA. There are 150 respondents in this research and all are Accountancy students of the College of Management enrolled during the Second Semester of Academic Year 2008-2009. They were given questionnaires with questions under each of the stress factor classification with an additional simplified personality type test adapted from Jenkins activity Survey (1971) in determining personality type as Type A or Type B. The results of the study show that among the perceived factors, academic sources of stress are deemed to be the most significant stress factors that affect the respondents' academic performances. This is followed by personality type, social and other factors, and financial factors. The degree of correlation between perceived stress factors and GWA was identified to be 66.9% significant through linear regression calculations. The research showed that stress factors can really have a positive and significant influence to a student's GWA (R = 0.669 and R2 = 0.448 at 5% level of significance), especially to a student who easily gets stressed as characterized by his or her personality type. The research further reveals that there are other factors that should be identified aside from the items included in this study to improve the strength as to how perceived stress factors affect the academic performance of BS accountancy students.
Business Research (BA 199-Business Research). -- [Iloilo City] : University of the Philippines Visayas - College of Management, December 2008.